Collection of triatomines from sylvatic habitats by a Trypanosoma cruzi-infected scent detection dog in Texas, USA - Christopher, Devin M.; Curtis-Robles, Rachel; Hamer, Gabriel L.; Bejcek, Justin; Saunders, Ashley B.; Roachell, Walter D.; Cropper, Thomas Leo; Hamer, Sarah A. (PLOS Neglected Tropical Diseases, 2023)
Author summary Triatomine insects, also known as ‘kissing bugs,’ are vectors of Trypanosoma cruzi, the parasite that causes Chagas disease in humans, dogs, and other mammals. Triatomines are found throughout the Americas, but for many species, little is known about where these blood-sucking insects spend their early life stages. Knowing more is important to vector control initiatives aimed at preventing Chagas disease. Scent detection dogs have been trained to detect many pests, including one study in Paraguay of a dog trained to detect triatomines. In this study, we used a dog to detect triatomines in their natural environments throughout Texas. Over 6 weeks, the dog identified 60 triatomines at 6 different sites; an additional 50 triatomines were collected without the dog’s assistance. More triatomines were collected per hour when the dog was searching when compared to only humans searching. Of all the triatomine nymphs collected, 27% were positive for T. cruzi, and bloodmeal analyses revealed kissing bugs had fed on Southern plains woodrat, opossum, and eastern cottontail. This study outlines a strategy that can be replicated in the United States to enhance the detection and control of habitats where triatomines spend their early life stages.